Hasil Belajar Materi Pengukuran Di Sekolah Dasar Dengan Model Pembelajaran Problem Based Learning - Melani Khalimatu Sa’diyah; Sefhiana Andara; Zulfa Ishmah Rahadatul Aisy; Prihatini Prihatini (Universitas Palan, 2024)
This article discusses the application of the Classroom Action Research (PTK) method with the Problem Based Learning (PBL) learning model to improve learning outcomes in measurement material in elementary schools. The PTK method is an effective approach in identifying learning problems, formulating solutions, and testing their effectiveness directly in the classroom. The PBL model, as a student-centered learning approach, has been proven effective in improving student learning outcomes in measurement material in elementary schools. In the context of measurement, the application of the PBL model is expected to strengthen students' understanding of basic measurement concepts, such as units of measurement, measuring tools, and their application in the context of everyday life. PBL offers a student-centered learning approach, which not only helps students understand mathematical concepts, but also encourages active involvement, problem solving, and the development of critical thinking skills.